The impact of initial tumor microenvironment on imaging phenotype. (2021) - Nagaraja, Tavarekere N.; deCarvalho, Ana C.; Brown, Stephen L.; Griffith, Brent; Farmer, Katelynn; Irtenkauf, Susan; Hasselbach, Laura; Mukherjee, Abir; Bartlett, Seamus; Valadie, O. Grahm; Cabral, Glauber; Knight, Robert A.; et al.
Highlights: Most available murine models of glioblastoma (GBM) do not reproduce radiologic features of the human disease i.e., a space-occupying tumor and T1 contrast enhancement on MRI. Attempts have been made to generate such models by serial in vivo passaging of GBM cells. This work describes a simple method to generate such tumors in the first generation of implanted rats by co-injection of Matrigel during tumor implantation. Abstract: Models of human cancer, to be useful, must replicate human disease with high fidelity. Our focus in this study is rat xenograft brain tumors as a model of human embedded cerebral tumors. A distinguishing signature of such tumors in humans, that of contrast-enhancement on imaging, is often not present when the human cells grow in rodents, despite the xenografts having nearly identical DNA signatures to the original tumor specimen. Although contrast enhancement was uniformly evident in all the human tumors from which the xenografts' cells were derived, we show that long-term contrast enhancement in the model tumors may be determined conditionally by the tumor microenvironment at the time of cell implantation. We demonstrate this phenomenon in one of two patient-derived orthotopic xenograft (PDOX) models using cancer stem-like cell (CSC)-enriched neurospheres from human tumor resection specimens, transplanted to groups of immune-compromised rats in the presence or absence of a collagen/fibrin scaffolding matrix, Matrigel. The rats were imaged by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and their brains were examined by histopathology. Targeted proteomics of the PDOX tumor specimens grown from CSC implanted with and without Matrigel showed that while the levels of the majority of proteins and post-translational modifications were comparable between contrast-enhancing and non-enhancing tumors, phosphorylation of Fox038 showed a differential expression. The results suggest key proteins determine contrast enhancement and suggest a path toward the development of better animal models of human glioma. Future work is needed to elucidate fully the molecular determinants of contrast-enhancement.